Advances in Resist Materials and Processing Technology XXV 2008
DOI: 10.1117/12.772012
|View full text |Cite
|
Sign up to set email alerts
|

Plasma etch properties of organic BARCs

Abstract: Plasma etching is an integral part of semiconductor integrated circuit (IC) processing and is widely used to produce high-resolution patterns and to remove sacrificial layers. Bottom anti-reflective coatings (BARCs) under the resist absorb light to minimize reflectivity during lithography and are typically opened during pattern transfer using plasma etching. High etch selectivity is required in the BARC opening process to minimize resist loss to allow further substrate etching. Because the plasma etch process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The Ohnishi parameter is a popular empirical correlation that relates the atomic composition of the polymer, in particular, the number of carbon and oxygen atoms. 9,10) The Ohnishi parameter was calculated according to…”
mentioning
confidence: 99%
“…The Ohnishi parameter is a popular empirical correlation that relates the atomic composition of the polymer, in particular, the number of carbon and oxygen atoms. 9,10) The Ohnishi parameter was calculated according to…”
mentioning
confidence: 99%
“…In earlier studies, incorporation of halogen atoms, specifically fluorine and bromine into polymers was found to induce slower etch rate under O2 oxidizing gas and faster etch rate under CF4 reducing gas. 3,4 However, a literature review revealed that there is very limited work done to understand the effect of iodine elements on etch properties of advanced EUV resist. Figure 2 shows the etch rate results of 3 different formulations (Resist-1, Resist-2, and Resist-3) under O2 (Figure 2-A) and CF4 (Figure 2-B) plasma etch conditions plotted with adjusted Ohnishi Parameter (OP) on the x-axis.…”
Section: Resultsmentioning
confidence: 99%
“…The surface fluorine content change before and after CF4 plasma etching is in an agreement with the earlier result reported by Huang and Weigand. 3 It is believed that during CF4 etching, fluorine replaces hydrogen or substitutes other groups to form a protective film on the organic (resist) surface. 3,6 It is important to note that XPS results confirm that Resist-3 contains the highest iodine content, followed by Resist-2 and Resist-1 at 0 sec etching time (Figure 7-D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is so-called ultra-narrow via in 3D NAND flash. In the industry, anti-reflective coating (ARC) etching of ultra-narrow via usually uses CF 4 , Ar, O 2 , CHF 3 , CO, Cl 2 [5][6][7] etc. CO 2 , COS, O 2 , C 4 F 8 , SF 6 , Ar etc., are usually used during hard mask etching.…”
mentioning
confidence: 99%